АРТУР КОНАН ДОЙЛЬ ИЛМИЙ ФАНТАСТИКАСИДА ИНСОН ОМИЛИ ТАЛҚИНИ. - Narbekov, Farxod (Журнал иностранных языков и лингвистики, 2021)
Тhis article deals with the influence of scientific imagination to the human soul in the world culture. The article is about the catastrophic impact of morality on the human heart in the world culture